Analisis Barrier to Adoption (Hambatan Untuk Mengadopsi) Aplikasi Ojek Online oleh Ojek Konvensional - Roland H. Pakpahan; Henry Pandia (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2018)
At this moment, ojek is one of alternative transportation that has been choosed by most people, this is because ojek offered a solution for trafics in capital city. The development of technology by the appereance of online ojek that give convenience to consumen who use application that intregrated to the company, so the convenience that offered by online ojek seems like drown conventional ojek and cause them loss income. This reseach is to find the obstacles for conventional ojek driver to join online ojek. The purpose for this reseach is to know what are the barrier to adopt online ojek application in the circles of conventional ojek driver and to find solution to reduce the barrier to adoption to technology by conventional ojek driver. As for as we found 6 components for the barrier, such as behavior and consumen behavior, technology, financial, completeness for ride, information and paguyuban. the sixth component measured on 36 respondents in Bandung area, and all the respondent is ojek conventional drivers. Collecting data by interview and spreading questionnaire for processing data. This research is descriptive research that show object and event to know the circumstances that happend now and to illustrate the solution for barrier of aplication adoption by conventional ojek driver. Author take conclution based on questionnaire that the biggest barrier component from all component is paguyuban to adopt online application, where as they still comfortable to wait for their customer in their spot, this cause by the feeling togetherness each other and it reduces competition, based on the analysis of data, author give some suggestion to reduce the barrier to adopt online aplication that is education is important fact to increase how people think, from society it is one of the important things to become a productive and eficient work in the future.